A comparison of sexual risk behaviour between HIV positive and HIV negative men in Gauteng and the Western Cape - Mabuza, Hloniphile Innocentia (My University, 2014)
South Africa continues to grapple with the HIV/AIDS epidemic almost 30 years since the disease was first described. South Africa has 6.4 million people living with HIV thereby contributing 17% to the global burden of HIV/AIDs even though it makes up 0.7% of the world population translating to an HIV prevalence of 10.6% in the general population. . Multiple concurrent sexual partnerships (MCP) and inconsistent condom use are notably the major contributors to the spread or transmission of HIV in South Africa. The South African government has allocated massive financial resources to support HIV/AIDS interventions, however, the epidemic continues to amplify in South Africa and there is a growing need for targeted HIV prevention interventions which will address behaviour change. Objectives The objectives of the study were to determine the differences in sexual risk behaviour between self-identified HIV positive and HIV negative men and identify factors associated with sexual risk behaviour. Methodology This was secondary data analysis of a cross sectional design study called "Risk Perceptions of HIV Positive Men" and it was conducted in clinics from Soweto, Cape Town and the Cape Winelands from October 2010 to July 2011. The sample size was 451 and the study population comprised self-identified HIV positive and negative men between ages 18 - 60 years. Proportion of consistent condom use (CCU) and multiple concurrent partnerships (MCP) were calculated and difference between those self-identified HIV positive and negative were determined using Chi-square tests. Factors associated with MCP and CCU between the two groups was determined using univariable and multivariable logistic regression Results We analysed data for 451 men with a mean age of 39 years (std. dev. 11.30). Out of the 451 men 311 (69%) identified themselves as HIV positive and there was a statistical significant difference in baseline characteristics between HIV positive and HIV negative men (age, race, relationship status, employment status, education level, religion, area of residence, age at sexual debut, condom use at first sex, sexual orientation and circumcision status). HIV positive men were four times more likely to have used condoms consistently in the last six months compared to HIV negative men (AOR=3.72, CI: 1.95-7.11), however, HIV positive men were also four times more likely to have had Multiple Concurrent Partnerships in the last 12 months compared to HIV negative men (AOR=4.60, CI: 2.09- 10.12) . Other factors associated with sexual risk behaviour were; relationship status, age group, race, age at sexual debut, alcohol frequency, sexual orientation and perceptions about undetectable viral load reducing HIV transmission risk. Conclusion and recommendation There is a difference in sexual risk behaviour between men who identified themselves as HIV positive and those who identified themselves as HIV negative. Men who identified themselves as HIV negative were less likely to have used condoms consistently in the last six months. Though the HIV positive men are using condoms consistently they have multiple concurrent partners. There is need to strengthen post HIV test counselling coupled with targeted messages for both HIV positive and HIV negative men.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology in the field of Infectious Diseases School of Public Health, University of the Witwatersrand May 2014
Keywords: Sexual Behavior--South Africa; HIV--prevention & control